2010
DOI: 10.1093/pcp/pcq053
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transport Mediated by Arabidopsis TGD Proteins is Unidirectional from the Endoplasmic Reticulum to the Plastid

Abstract: The transfer of lipids between the endoplasmic reticulum (ER) and the plastid in Arabidopsis involves the TRIGALACTOSYLDIACYLGLYCEROL (TGD) proteins. Lipid exchange is thought to be bidirectional based on the presence of specific lipid molecular species in Arabidopsis mutants impaired in the desaturation of fatty acids of membrane lipids in the ER and plastid. However, it was unclear whether TGD proteins were required for lipid trafficking in both directions. This question was addressed through the analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…The rationale for the screen is based on extensive genetic evidence showing that the fad6 mutant is dependent on import of polyunsaturated lipid precursors from the ER for thylakoid lipid assembly (Browse et al, 1989), a process involving TGD proteins (Xu et al, 2010). Whereas the fad6 mutant itself is similar to the wild type in terms of growth and development, the fad2 fad6 double mutant, which is deficient in the conversion of 18:1 to 18:2 in both the ER and plastids, is chlorotic because polyunsaturated fatty acids that are necessary for a competent photosynthetic membrane system are lacking (McConn and Browse, 1998).…”
Section: Isolation Of the Tgd5 Mutantmentioning
confidence: 99%
“…The rationale for the screen is based on extensive genetic evidence showing that the fad6 mutant is dependent on import of polyunsaturated lipid precursors from the ER for thylakoid lipid assembly (Browse et al, 1989), a process involving TGD proteins (Xu et al, 2010). Whereas the fad6 mutant itself is similar to the wild type in terms of growth and development, the fad2 fad6 double mutant, which is deficient in the conversion of 18:1 to 18:2 in both the ER and plastids, is chlorotic because polyunsaturated fatty acids that are necessary for a competent photosynthetic membrane system are lacking (McConn and Browse, 1998).…”
Section: Isolation Of the Tgd5 Mutantmentioning
confidence: 99%
“…The TGD1, TGD2 and TGD3 proteins form a bacterial-type ABC transporter (ATP-binding-cassette transporter) in the inner envelope of chloroplasts touching the outer envelope [17]. TGD1 is a permease and TGD3 is an ATPase providing the energy for lipid transport [11,25,56], probably making the lipid transfer from the ER to the chloroplast unidirectional [57]. TGD2 has an N-terminal transmembrane domain and a C-terminal soluble domain facing the intermembrane space [58].…”
Section: The Er-chloroplast Contact Sitementioning
confidence: 99%
“…increased, 14 suggesting a decreased ratio of plastid-to-extraplastidic membranes in the double mutants. In support, ultrastructural analysis revealed that the thylakoid membrane systems in double mutants were severely underdeveloped with almost no grana stacking, particularly in the tgd4-3 fad6-1 double mutant.…”
mentioning
confidence: 95%
“…In both tgds fad6-1 and tgd4-1 ats1-1 double mutants, there were more than 50% reductions in levels of MGDG with concomitant increases in phospholipids, particularly PC. 9,14 Whether these lipid changes are the cause of the chloroplast division defects in the double mutants can not be ascertained at this time. However, it has been shown that a similar extent of reduction in the level of MGDG in the pgp1 mutant does not compromise chloroplast division.…”
mentioning
confidence: 99%